2013
DOI: 10.1227/neu.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

Is Intraoperative Diffusion Tensor Imaging at 3.0T Comparable to Subcortical Corticospinal Tract Mapping?

Abstract: The linear current-distance correlation was found both in pre-iMRI and in post-iMRI data. Intraoperative image distortion appeared in 36%. Neurophysiological subcortical mapping remains superior to DTT. Combining these 2 methods in selected cases can help increase the safety of tumor resection close to the CST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 47 publications
1
21
0
4
Order By: Relevance
“…We summarize the existing literature in Table 1. These reports support a high linear correlation between distances to reconstructed tracts and positive DES intensities (Javadi et al, 2017, Maesawa et al, 2010, Ostry et al, 2013) or post-operative deficits (Prabhu et al, 2011). In addition to intra-operative morphological data, DTI sequences can be relatively quick to acquire and could be obtained intra-operatively in operating rooms with intra-operative MRI capability.…”
Section: Supratentorial Lesionssupporting
confidence: 63%
“…We summarize the existing literature in Table 1. These reports support a high linear correlation between distances to reconstructed tracts and positive DES intensities (Javadi et al, 2017, Maesawa et al, 2010, Ostry et al, 2013) or post-operative deficits (Prabhu et al, 2011). In addition to intra-operative morphological data, DTI sequences can be relatively quick to acquire and could be obtained intra-operatively in operating rooms with intra-operative MRI capability.…”
Section: Supratentorial Lesionssupporting
confidence: 63%
“…Consequently, this study was not designed to measure the accuracy of the tractography results intraoperatively. To answer this additional research question and to further validate DTI tractography results, future studies are required which either use intraoperative MRT/DTI (Nimsky et al, 2005a, Nimsky et al, 2005b, Nimsky et al, 2006, Nimsky, 2011, Ostrý et al, 2013, Shahar et al, 2014) or avoid the brain shift by means of stereotactic approaches (Forster et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…As reported by Ostry et al, 34 5 studies performed a quantitative analysis of the relationship between the distance from CST and the stimulation intensity but provided variable results. [33][34][35][36][37] Among these studies, 4 found a linear correlation between the distance and the stimulation intensity, 33-36 whereas a nonlinear relationship was found in 1 study.…”
Section: Discussionmentioning
confidence: 99%